SYNTHESIS, CRYSTAL STRUCTURE OF A NOVEL 1D CHAINED Na(I) COORDINATION POLYMER MATERIALS BASED ON SCHIFF-BASE LIGAND - LI-HUA WANG (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
A novel 1D chained Na(I) coordination polymer materials has been obtained by reaction of 2-hydrazinobenzoic acid with 2-formyl-benzenesulfonic acid sodium salt in CH3CH2OH/H2O. It was characterized X-ray single crystal diffraction analysis. The crystal of the Na(I) coordination polymer belongs to triclinic, space group P-1 with a = 6.0354(12) Å, b = 8.1922(16) Å, c = 18.729(4) Å, α = 93.70(3)º, β = 95.68(3)º, γ = 97.03(3)º, V = 911.8(3) Å3, Z = 2, Dc = 1.444 μg·m-3, μ= 0.245 mm-1, F(000)= 412, and final R1 = 0.0833, ωR2 = 0.2867. X-ray analysis reveals that each Na(I) center is six-coordination with a O6 distorted octahedron coordination environment. The Na(I) ions are linked through the O atoms of sodium 2-{(E)-[2-(2-carboxyphenyl) hydrazinylidene]methyl}benzenesulfonate to form 1D chain coordination polymer.